Design of Work Facilities to Reduce Complaints of Musculoskeletal Disorders (MSDS) with an Ergonomic Approach to Coffee Farmers - Nukhe Andri Silviana; Chalis Fajri Hasibuan; M. Fauza Rizkyansyah (International Journal of Health Engineering and Technology, 2022)
Complaints on the musculoskeletal system are complaints that are felt by a person in the muscles and skeleton with different levels of complaints, complaints to this damage are usually referred to as musculoskeletal disorders. The purpose of this study was to improve work facilities in the process of picking coffee cherries in Arul Item Village, Central Aceh. This measurement was carried out using the REBA (Rapid Entire Body Assessment) method and using the NBM (Nordic Body Map) questionnaire as the research instrument. The study was conducted using an analytical survey method which aims to see the relationship between work attitudes and musculoskeletal complaints with an ergonomic approach. From the results of the NBM questionnaire on 56 workers, it shows that the musculoskeletal complaints experienced by coffee berry pickers are in the category of pain, most of which are in the upper neck and left wrist as many as 39 (70%). In the very category of pain, the most pain was in the left shoulder 50 (89%) and the right wrist as much as 33 (59). Based on measurements using the REBA method, it is stated that there is an actual REBA score of 4-7 where the risk is at moderate risk for musculoskeletal disorders and on the proposed REBA score there is a score of 2 where the score is in a low risk area, so as to improve work attitudes and work posture which resulted in the emergence of musculoskeletal complaints, a modified work tool design, namely a bag, was proposed to reduce the high number of musculoskeletal complaints in coffee fruit pickers